Marital maladjustment and its relationship to the emergence of borderline personality disorder symptoms in abused women - Alhajaj, Majdi (Edelweiss Applied Science and Technology, 2025)
The dysfunctions and disputes that impede the emotional and psychological health of partners in a marriage are referred to as marital maladjustment. Communication problems, emotional neglect, and physical or emotional abuse are some of the ways this maladjustment might manifest. These issues can significantly impact mental health, especially when abusive relationships are involved. This study examines the connection between marital maladjustment and the development of borderline personality disorder symptoms in abused women, as marital maladjustment may contribute to the manifestation of personality disorder symptoms in this population. A questionnaire was developed to investigate and establish a relationship between marital maladjustment and the emergence of borderline personality disorder symptoms in abused women. The sample consisted of 50 abused women exhibiting borderline personality disorder symptoms from various environments and regions in Jordan. The questionnaire comprised two sections: the first gathered demographic information, and the second contained 20 questions related to the core issue. The collected data were tabulated, analyzed, and discussed using appropriate statistical methods. Results indicated that 40% of the women reported that their husbands used violence for any reason or without reason, and 40% stated that their husbands beat them due to their mental illness. Additionally, 30% attributed the violence to their husbands’ alcoholism. Furthermore, 60% of the sample identified inadequate housing as a cause of family violence, while 70% linked it to low family income. Regarding causes of violence, 70% cited discrimination between boys and girls within the family. Half of the participants acknowledged witnessing violence during childhood, which they believed contributed to their own victimization later. Moreover, 80% reported that their husbands used foul language during abuse, and 70% experienced physical violence with hard tools. The women in the sample reported suffering from physical injuries and psychological illnesses, with prevalence rates ranging from 60% to 90%. The study concludes that marital maladjustment has a significant effect on the development of borderline personality disorder symptoms in women. Childhood experiences of abuse also significantly influence the emergence of personality disorder symptoms. Marital maladjustment and the appearance of borderline personality disorder symptoms in abused women have notable effects on families. Finally, social problems and family income significantly impact marital maladjustment and the development of personality disorder symptoms in married women.